Body somatotype and dietary intakes of government employees in Kuala Terengganu - Khairil Shazmin Kamarudin; Wan Abdul Manan W.M. (Penerbit Universiti Kebangsaan Malaysia, 2019)
Nutritional intake is one of the most important aspects that influence body composition and may affect body somatotype. Some previous studies conducted on somatotype in Malaysia have focussed on the aspect of sport performance and physical activities but none were on somatotype with dietary intakes. Thus, this study was conducted to determine the relationship between somatotype and dietary intakes. A total of 308 males and females of uniformed government agencies personnel in Kuala Terengganu were systematically selected to participate into this study. Somatotype was determined by using the Heath and Carter, method. Dietary intakes were measured by using 24-hour dietary recall technique. The mean age of respondents was 38.18 ± 5.23 years. Their mean BMI was 26.09 ± 5.69 kg/m2, which indicated that they were overweight. Mean somatotype components of the male respondents were (5.71, 4.73, 1.20), while of female respondents were (8.77, 4.99, 0.77). This indicated that the males belonged to mesomorph-endomorph body somatotype while the females belonged to mesomorph endomorph somatotype category. Median calories intake among respondents was 1987 kcal per day. The correlation between endomorphy component with calories, carbohydrate and protein intake were r= -0.083, r= -0.172 and r= -0.226, respectively (p<0.05). Mesomorphy component correlated negatively with protein intake of respondents (r= -0.161, p<0.05). The ectomorphy component correlated positively with calories (r= 0.151, p<0.05), carbohydrate (r= 0.113, p<0.05), protein (r= 0.191, p<0.05) and fat intake (r=0.112, p<0.05). Some vitamins and minerals intake also shows correlation with somatotype components. Generally, this study suggested that dietary intakes influence somatotype components and somatotype measurements can be useful to be used as tools for identifying obesity predispositions.